Plant communities and phytogeographical units from NW San Juan Province (High Central Andes of Argentina) - Martinez Carretero, Eduardo Enrique (2010)
Vegetation of the High Central Andes of Argentina was studied in NW San Juan Province (MAB Reserve of San Guillermo) from a phytosociological point of view. Four new associations are proposed: two shrubland associations, Artemisietum paramilloensis and Lycio-Ephedretum rupestri, and two grassland associations, Jaravetum chrysophyllae and Jaravetum absconditae. The latitudinal and altitudinal boundaries of the Monte, Puna and High Andean phytogeographic provinces were established for the study area. This area constitutes the floristic and biogeographic transition between northern (Bolivia) and southern (Mendoza, Argentina) Puna elements, belonging to the Calamagrostietea vicunarum class, and to the Stipo-Lycietea class, respectively.